Intestinal parasitic infections in children presenting with diarrhoea in outpatient and inpatient settings in an informal settlement of Nairobi, Kenya - Mbae, Cecilia Kathure (BioMed Central, 2013)
BACKGROUND: The distribution of and factors associated with intestinal parasitic infections are poorly defined in high risk vulnerable populations such as urban slums in tropical sub-Saharan Africa. METHODS: In a cross sectional study, children aged 5 years and below who presented with diarrhoea were recruited from selected outpatient clinics in Mukuru informal settlement, and from Mbagathi District hospital, Nairobi, over a period of two years (2010–2011). Stool samples were examined for the presence of parasites using direct, formal-ether concentration method and the Modified Ziehl Neelsen staining technique. RESULTS: Overall, 541/2112 (25.6%) were positive for at least one intestinal parasite, with the common parasites being; Entamoeba histolytica, 225 (36.7%),Cryptosporidium spp. 187, (30.5%), Giardia lamblia, 98 (16%).The prevalence of intestinal parasites infection was higher among children from outpatient clinics 432/1577(27.4%) than among those admitted in hospital 109/535 (20.1%) p < 0.001. Infections with E. histolytica, and G. lamblia were higher among outpatients than inpatients (13.8% vs 1.3% p < 0.001 and 5.8% vs 1.3% p < 0.049) respectively, while infection with Cryptosporidium spp. was higher among inpatients than outpatients (15.3% vs 6.7%) respectively p < 0.001. Other parasites isolated among outpatients included Isospora belli, 19 (1.2%), Ascaris lumbricoides, 26 (1.6%), and Hymenolepis nana 12 (0.8%), with the remainder detected in less than ten samples each. HIV-infected participants were more likely to be infected with any parasite than uninfected participants, Adjusted Odds Ratio (AOR), 2.04, 95% CI, 1.55-2.67, p < 0.001), and with Cryptosporidium spp. (AOR, 2.96, 95% CI 2.07-4.21, p < 0.001).The inpatients were less likely to be infected with E. histolytica than outpatients (AOR, 0.11, 95% CI, 0.51- 0.24, p < 0.001), but more likely for inpatients to be infected with Cryptosporidium spp. than outpatients (AOR, 1.91, 95% CI, 1.33-2.73, p < 0.001). Mixed parasitic infections were seen in 65 (12.0%) of the 541 infected stool samples. CONCLUSION: Intestinal parasitic infections are common in urban informal settlements’ environment. Routine examinations of stool samples and treatment could benefit both the HIV infected and uninfected children in outpatient and inpatient settings.